2013
DOI: 10.1108/s1474-8231(2013)0000015009
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal and Vertical Integration of Physicians: A Tale of Two Tails

Abstract: This is the first comprehensive review of the scale and scope economies of physician practice in nearly two decades. The research results do not appear to have changed much; nor has much changed in physician practice organization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
110
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(113 citation statements)
references
References 94 publications
3
110
0
Order By: Relevance
“…This can occur through the exercise of managerial control under an employment contract or financial rewards such as call pay, directorships, and ancillary service agreements (Burns et al, 2013). Optimists about integration think that this reduces agency problems.…”
Section: Introductionmentioning
confidence: 98%
“…This can occur through the exercise of managerial control under an employment contract or financial rewards such as call pay, directorships, and ancillary service agreements (Burns et al, 2013). Optimists about integration think that this reduces agency problems.…”
Section: Introductionmentioning
confidence: 98%
“…These various arrangements could provide physician organizations with greater resources, which need not necessarily enhance clinical decisions, as they could support higher physician incomes rather than support patients' ongoing care. 41 Formal employment of physicians by hospitals and other entities, however, could reduce physician autonomy and affect evidence based-decisions at the point of care either positively or negatively, depending, for instance, on whether the employer's focus tilts toward quality improvement or revenue maximization.…”
Section: Network and Affiliationsmentioning
confidence: 99%
“…3 In a recent review of literature on scale and scope economies in physician practice organizations, Burns and colleagues noted there has been rapid growth in very large physician practices, but that most physicians continue to practice in smaller and single-specialty practices. 4 Further, Burns et al found the Bevidence of scale economies, scope economies, and quality performance advantages [for larger groups] has been strikingly thin, in some cases for decades.^Given ongoing physician payment reforms, and concerns these can motivate opportunistic integration of physicians into larger organizational entities of uncertain value to patients, 5-7 the impact of practice consolidation on the economics of physician practice remains an important policy research question.…”
Section: Introductionmentioning
confidence: 99%
“…Utilizing the recent review by Burns et al, 4 as well as supplemental searches of EBSCOhost, PubMed and MEDLINE, and Google Scholar for articles published since 1980, we review practice inputs and outputs as typically described in the literature on the economics of medical practice, as well as new considerations relevant to the evolving nature of physician work. We identify the conceptual challenges for defining these Binputs^and Boutputs^in a complex and evolving health care system.…”
Section: Introductionmentioning
confidence: 99%